Contribution of downstream promoter elements to transcriptional regulation of the rice tungro bacilliform virus promoter - He, Xiaoyuan (Oxford University Press, 2002)
Downstream sequences influence activity of the rice tungro bacilliform virus (RTBV) promoter in protoplasts derived from cultured rice cells. We previously identified a DNA element located between positions +50 and +90 relative to the transcription start site to which rice nuclear proteins bind. In this study, using DNA UV crosslinking assays, we show that two rice nuclear proteins bind specifically to this DNA element. We demonstrate that the DNA element enhances RTBV promoter activity in a copy number-dependent manner when transferred to a position upstream of the promoter. In addition, using electrophoretic mobility shift assays, we show that at least two novel nuclear proteins from rice cell suspension cultures bind to a subregion (from +50 to +59) of the DNA element and that a protein from rice root, but not shoot, nuclear extracts interacts with a perfect palindromic sequence motif located within the sequence +45 to +59. Furthermore, a position-dependent GAGA motif, present in three copies within downstream promoter sequences from +1 to +50, is involved in the regulation of RTBV promoter activity.